2013 IEEE 26th International Conference on Micro Electro Mechanical Systems (MEMS) 2013
DOI: 10.1109/memsys.2013.6474298
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic micromotor autonomously movable in biofuels

Abstract: Zinc/platinum (Zn/Pt) bimetallic micromotors have been developed. They moved based on the reduction of fuel compounds such as bromine, p-benzoquinone, and methanol at the surface of the Pt and the oxidation (dissolution) of Zn that occur simultaneously. The redox potential of Zn 2+ /Zn is very negative and was advantageous to cause the redox reactions. The motion of the motor and the reactions that occurred on the surface were investigated. With test motors containing Ni, it was revealed that the Zn/Pt motors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Synthetic nano-and micromotors, when powered by chemical fuels, exhibit motility when they sense specific chemicals, e.g., hydrogen peroxide (1,110), halogen (38), p-benzoquinone (111), and glucose (40). The motility is affected only by its local environment.…”
Section: Chemical Sensing With Synthetic Motorsmentioning
confidence: 99%
“…Synthetic nano-and micromotors, when powered by chemical fuels, exhibit motility when they sense specific chemicals, e.g., hydrogen peroxide (1,110), halogen (38), p-benzoquinone (111), and glucose (40). The motility is affected only by its local environment.…”
Section: Chemical Sensing With Synthetic Motorsmentioning
confidence: 99%
“…However, microscale selfpropulsion is not confined to the biological realm. Inspired by swimming microorganisms, the design of many synthetic swimmers has attempted to reproduce the motions of appendages such as cilia (Dreyfus et al 2005, Sanchez et al 2011 or flagella (Ghosh & Fischer 2009, Zhang et al 2010), which are found on both eukaryotic and prokaryotic cells. This motion must be actuated by external forces, such as those exerted by magnetic fields, and thus most synthetic mechanical swimmers are not truly autonomous motors.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial micro/nanomotors are tiny objects that can autonomously move under the influence of an appropriate source of energy, such as chemical fuels, , magnetic field, , electrical field, , ultrasound, , or light , and so forth, and hold considerable promise for diverse future applications. Catalytic nanomotors are one of the most attractive types of micro/nanomotors which can convert local chemical fuel in solution into mechanical work, and they exhibit outstanding potentials in various fields, ranging from environmental remediation , to biomedical applications. , However, most self-propelled systems reported so far, such as metallic nanowires, , microtubular microrockets, , Janus micro-spheres, , and supermolecule-based nanomotors, , require toxic chemical fuels (H 2 O 2 , I 2 , Br 2 , and N 2 H 4 ), greatly limiting their practical applications. As a result, operating artificial micro/nanomotors efficiently with biocompatible fuels in order to broaden their practical applications is still a great challenge in nanotechnology.…”
Section: Introductionmentioning
confidence: 99%